Changes in cerebral autoregulation and vasoreactivity after surgical aortic valve replacement: a prospective study. Issue 1 (20th November 2022) - Pedro, Tiago; Costa, Andreia; Ferreira, Juliana; Rocha, Ana Luísa; Salgueiro, Elson; Pereira, Gilberto; Azevedo, Elsa; Castro, Pedro
Abstract : New Findings: What is the central question of this study? How are dynamic cerebral autoregulation and brain vasoreactivity influenced by severe aortic stenosis and its surgical treatment? What are the main findings and their importance? Dynamic cerebral autoregulation is preserved in the long term in patients with severe aortic stenosis and does not change after surgical aortic valve replacement. However, carbon dioxide vasoreactivity is impaired in these patients. Abstract: Surgical aortic valve replacement (SAVR) alters the natural course of severe aortic stenosis (AS). In this study, we aimed to determine the effects of the disease on dynamic cerebral autoregulation and vasoreactivity (VR) and to assess their changes after SAVR. We recruited 23 patients diagnosed with severe AS eligible for SAVR and 15 healthy matched controls. AS patients had lower mean VR to CO2 ( P  = 0.005) than controls, but dynamic cerebral autoregulation was preserved. Cerebral haemodynamics showed no significant change after SAVR. Patients with smaller baseline aortic valve areas presented with smaller low frequency phase changes after surgery ( P  = 0.016). Severe AS does not seem to impact dynamic cerebral autoregulation but does reduce VR to CO2 . SAVR does not alter cerebral autoregulation nor vasoreactivity.